Assessment of ecological and public health risks associated with heavy metals on farmland in Wonosobo Regency, Indonesia - Handayani, Cicik Oktasari; Sukarjo, Sukarjo; Zu'amah, Hidayatuz; Hidayah, Anik (Brawijaya University, 2024)
The deposition of metallic substances on farmland is of critical importance owing to its possible detrimental impacts on the surroundings and human wellness. Heavy metals can adversely affect the physicochemical properties of soil and plant health. Prolonged exposure to heavy metals in humans can lead to both carcinogenic and non-carcinogenic effects. The present research intended to determine the dispersion condition of toxic metals on cropland and assess the attendant environmental and health dangers in the Wonosobo Regency. This study used a soil sample survey encompassing 312 soil sampling sites. The completed analyses comprise geographical analysis, index of geo-accumulation (IG), contamination index (CI), Nemerow comprehensive contamination index (NCCI), risk analysis, and health risk analysis. The research findings reveal that cadmium material is the primary contributor to contamination from heavy metals in farmland in Wonosobo Regency, as shown by IG analysis. The CI and environmental hazards assessments suggest considerable pollution levels. Kids are more prone to illnesses than adults due to their daily intake amount, so it is necessary to pay more attention to the daily intake sources in children to minimize exposure to heavy metals.